Ontologi Pendidikan Islam: Studi Lapangan tentang Konsep Kemanusiaan di Pondok Pesantren Terpadu Daarul Furqon Sumedang - Rohim, Muhammad Syifa’ur; Nugraha, Mulyawan Syafwandi (Peneliti.net, 2025)
The notion of humans, educational goals, learners, teachers, and the learning process are the five main components of education that are important to examine in the science of education. Because humans are educable (students) and educated (educators), and because they are the intended and intended in the learning process and educational goals, they are the most basic and important of the five components of educational science to do so, hence the term “homo educabile” for humans. This research is classified as qualitative because it relies on qualitative data for its analysis. This research will be conducted at the Integrated Islamic Boarding School Daarul Furqon Sumedang. Methods in this research through interviews and observations are used to obtain data. These two methods are used to collect information and research data, especially about the concept of humanity. The results of the implementation of the concept of humanity by teachers or teachers show good results, because the reaction of students when discussing humanitarian values, the majority of students are enthusiastic because they realize that humanitarian values are very important for their own person in addition, the teacher always emphasizes that relationships between friends or even humans are very important because we live must need other people because humans are social creatures who cannot be separated from human relations.